Effect of Orem’s Self-Care Model on Perceived Stress in Adolescents with Asthma Referring the Asthma and Allergy Clinic, Isfahan, 2014 - Zeinab Hemati; Samira Abasi; Fatemehsadat Mosaviasl; Behzad Shakerian; Davood Kiani (International Journal of Community Based Nursing and Midwifery, 2016)
Background: Incidence of asthma in adolescents leads to variations in family status, roles and interaction with peers for them, which could be a source of stress and psychological tensions in them. Therefore, the present study was conducted to investigate the effect of Orem’s self-care model on perceived stress in adolescents with asthma. Methods: In this semi-experimental study conducted from April 2013 to February 2014, 64 asthmatic adolescents referring Shariati Hospital, Isfahan were enrolled by simple random sampling and the patients were assigned to two groups of control and intervention. Then, Orem’s self-care model-based training was implemented throughout eight sessions of two hours each and the Cohen Perceived Stress Scale was administered to both groups prior to and two months after the completion of the training. The data were analyzed by descriptive and analytical statistics consisting of paired t-test, independent t-test, Chi-square and Mann-Whitney using SPSS Version 20. Results: Mean age of the participants was 14.15±3.12 years in the intervention group and 15.21±3.09 years in the control groups. 68.8% and 59.4% of the participants were male in the intervention and control groups, respectively. Independent t-test indicated a significant difference in the mean scores of perceived stress in the intervention (25.46±5.31) and control groups (28.90±5.27) after the training. Also, the result of paired t-test indicated a significant difference in the mean score of perceived stress between before (29.18±5.27) and after (25.46±5.31) training. Conclusion: As the training based on Orem’s model had a positive effect on declining perceived stress in asthmatic adolescents, continuation of using these training interventions could contribute to ultimately achieving positive outcomes in health functions of these patients.